ANALISIS PENGONTROLAN DAN MONITORING PERANGKAT ELEKTRONIK BERBASIS JARINGAN INTERNET MENGGUNAKAN EDIMAX SP-1101W DENGAN APLIKASI EDIPLUG - Silvia Budi Ratnasari . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Edimax SP-1101W Smart Plug Switch is a tool to turn off and turn on the electric controlled remotely via smartphone using Ediplug application. Electronic devices that are connected to Edimax SP-1101W Plug Smart Switch as research material that is lamp and fan. From the results of research can be summed process control and monitoring can be done anywhere as available internet networks. The outcome average of internet access speed on researcher’s home area was 0,292 Mbps for downloading, 0,768 Mbps for uploading and ping (delay) is 178 ms. If compared to the TIPHON standard, ping value in the category of